2020
DOI: 10.29216/ueip.676145
|View full text |Cite
|
Sign up to set email alerts
|

YENİ BİR VERİ KAYNAĞI OLARAK GOOGLE TRENDS: GELECEK YÖNELİMİ ENDEKSİ İLE İLGİLİ BİR DEĞERLENDİRME / Google Trends As A New Data Source: An Evaluation Of The Future Orientation Index

Abstract: Web 2.0 ile birlikte oluşan etkileşimli ortam, yeni veri kaynaklarını beraberinde getirmiştir. Bu yeni veri kaynaklarından biri, Google arama motorunda yapılan sorgulara erişimi sağlayan Google Trends platformudur. Bu çalışmada, internet kullanıcılarının gelecek yıl hakkında geçmiş yıldan daha fazla bilgi arama derecesini ölçme amacı ile geliştirilen Gelecek Yönelimi Endeksi ele alınmıştır. Endeksi geliştiren araştırmacılar, bu endeks ile ekonomik veya sosyal göstergeler arasında saptanan anlamlı korelasyonlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The results obtained through Google Trends, reflecting online search interest, have become a new data source in many academic studies. Studies utilizing Google Trends data can be observed in various fields, from economics to the healthcare sector (Ayan, 2020). The search query conducted with Google Trends is intended to be shown as an example in Figure 1.…”
Section: Google Trendsmentioning
confidence: 99%
“…The results obtained through Google Trends, reflecting online search interest, have become a new data source in many academic studies. Studies utilizing Google Trends data can be observed in various fields, from economics to the healthcare sector (Ayan, 2020). The search query conducted with Google Trends is intended to be shown as an example in Figure 1.…”
Section: Google Trendsmentioning
confidence: 99%